Are we prepared to develop palliative actions in a ward? A literature review - Lara Cardoso; Diana Salgueiro; Sónia Novais (Instituto Politécnico de Viseu, 2017)
Introduction: The World Health Organization (2015) presents as barriers to improving access to palliative care the lack of training and awareness of health professionals. Objectives: Identify the preparation of nurses who provide care, in the acute hospital setting, to develop palliative actions. Methods: Integrative literature review, through the electronic research in the B-ON platform, using the expression: (nursing) AND (palliative care) AND (acute hospital setting) NOT (child* OR infant* OR adolescent*), obtaining six articles of primary studies. Results: Obtained studies are representative of a total of 2220 nurses. The articles showed that nurses from acute hospitals, despite being able to care for patients with palliative care needs, felt that training in this area would be important in order to better understand the needs of these patients. Conclusion: Nurses consider that they have competencies to provide care related to palliative care in acute care, although recognizing that they should be provided with more formation.